Persuade Mothers in Post Natal Ward for Timely Initiation of Breastfeeding - Verma, Mamtarani; Srivastava , Ratan K; Divakar, B. (National Journal of Community Medicine, 2011)
Objective: Timely initiation of breast feeding has been an important issue since last many decades. However, encouragement and early initiation of breast feeding gained momentum since last 20 years. The traditional wisdom and scientific research have proved that mother’s milk is the best. Design: It is a Cross sectional study conducted in urban tertiary care teaching hospital. Methods: a pretested semi-structured questionnaire was used to interview hospitalized mothers. This paper is the result of the interview of 600 women who delivered babies in the hospital. Their Details of socio-demographic features were enquired in addition to the questions related to their initiation of breast feeding after the birth of baby. Timely initiation of breast-feeding was calculated in this paper as percent of infants (0 - <12 months) who were put to the breast within one hour of delivery. Results: Out of all deliveries, breast feeding was timely initiated within one hour only by 1.0 percent of mothers. However 30 percent mothers initiated breast feeding within two hours. Conclusion: The observations of the present study support that the health functionaries must utilize the opportunity to persuade mothers in the postnatal ward after delivery of their babies for early initiation of breast feeding.